Outcomes of nonagenarians with acute coronary syndrome. (25th November 2020) - Echarte Morales, J; Cepas Guillen, P.L; Caldentey, G; Martinez Gomez, E; Borrego-Rodriguez, J; Vidal, P; Llagostera, M; Viana Tejedor, A; Benito Gonzalez, T; Flores-Umanzor, E; Quiroga, X; Perez De Prado, A; et al.
Abstract: Background: Myocardial infarction (MI) in nonagenarians is associated with high morbidity and mortality. Nonetheless, this population has typically been underrepresented in cardiovascular clinical trials. Objective: The aim of this study was to evaluate outcomes of nonagenarian patients presenting with MI who underwent either conservative or invasive management. Methods: We retrospectively included all consecutive patients equal to or older than 90yo admitted with non-ST segment elevation (NSTEMI) or ST segment elevation MI (STEMI) in four tertiary care centers between 2005 and 2018. Patients with type 2 myocardial infarction were excluded. We collected patients' baseline characteristic and procedural data. In-hospital and at 1-year follow-up all-cause mortality and major adverse cardiovascular events were assessed. Results: 523 patients (mean age 92.6±2 years; 60% females) were analyzed. Overall, 184 patients (35.2%) underwent percutaneous coronary intervention (PCI), increasing over the years, mostly in STEMI group (from 16% of patients in 2005 to 75% in 2018). PCI was preferred in those subjects with less prevalence of disability for activities of daily living (p<0.01). The use of a radial access (76.6%) and bare metal stents (52.7%) was predominant. No significant differences were found in the incidence of major bleeding events or MI-related mechanical complications between both strategies. During index hospitalization, 99 (18.9%) patients died. Whereas no differences were found in the NSTEMI group (p=0.61), a significant lower in-hospital mortality was observed in STEMI group treated with PCI (p<0.01). At one-year follow up, 203 (38.8%) patients died, most of them due to a cardiovascular cause (60.6%). PCI was related to a lower all-cause mortality in either NSTEMI (p<0.01) or STEMI groups (p<0.01) however, lower cardiovascular mortality was only found in STEMI group (p=0.03). Conclusion: An invasive approach was performed in over a third of nonagenarian patients, carrying prognostic implications and with a few numbers of complications. PCI seems to be the preferred strategy for STEMI in this high-risk population in spite of age. Funding Acknowledgement: Type of funding source: None